The unconsciousness and the family pathology - Vera, Ricardo (2001)
The study of the unconsciousness, an extremely complex reality is analyzed by the Psychoanalytic Theory. We cannot restrict the concept of the unconsciousness to the individual subjective field. The family is the closest context to the subjects in which he or she develops and therefore affects the interaction. The clinical theory and practice which emerges from this proposal is our goal and project.